PERANCANGAN APLIKASI PENJAMINAN MUTU SEBAGAI DATA PENDUKUNG BENCHMARKING PERGURUAN TINGGI (Infotekmesin, 2018)
One of information system management that can ease and support information and decision making that needed by medium and upper level management is to provide the easy of acces towards information within or outside that relates with the organization’s goal. This study was conducted in the higher education that has organization structure includes lower, medium and upper level management. The method that used was software delevoping method, i.e. waterfall. The result of this study is this information system can be used to support data menagement of quality assurance for support benchmarking of the higher education, obtain information of the higher education activities that agree with target or visi and mission, and also compare the progress of each unit in the higher education. Therefore, from the exsist studies, it can be easy for the executive boards to make policy and decision for running the higher education.